Destroying the Linear No-threshold Basis for Radiation Regulation - Carol S. Marcus (SAGE Publishing, 2016)
This article suggests five classes of effort that scientists can undertake to destroy the linear no-threshold hypothesis as the basis of radiation regulation in the United States. These are (1) pressure on regulators such as the Nuclear Regulatory Commission, (2) presidential messages, (3) Congressional pressure, (4) educate physicians about low-dose radiation, and (5) work with journalists and media people.